THE POTENTIAL OF USING VIDEO GAMES IN DISTANCE LEARNING GEOGRAPHY - Sadykova, Bagila; Esnazarova, U.; Tokbergenova, A. (Pedagogy and Psychology, 2022)
The article discusses the history of the development of such an important and integral part of modern life as video games, as well as the possibility of using video games in distance learning geography. The history of the development of video games reveals trends in their use in education. The advantages and disadvantages of using video games in education are identified, and the use of video games in the learning process is described as a concrete example. Describes the video games and programs currently used in education around the world.